Comprehensive analysis in mucin-producing urothelial-type adenocarcinoma of the prostate: case study with literature review - Moe, KyuKyu; Maa, Hung-Chune; Pei, Dee; Liang, Yao-Jen; Chen, Yen-Lin (Polish Journal of Pathology, 2020)
It is critical to distinguish the rare neoplasm of mucin-producing urothelial-type adenocarcinoma of the prostate (MPUAP) from either prostate origin or metastatic adenocarcinoma. This is mainly because they have different tumor staging, clinical behavior and treatment plans. In the current study, we try to fulfill the lack of knowledge in this field. There were totally 24 MPUAP cases including previous reported 23 cases and adding one new MPUAP case in the current study. We performed IHC and 78 genes panel analysis in two cases of ours. Most of the cases had urinary obstruction symptoms and normal PSA level. Pathological features showed dissection of the stroma by mucin pools and glands lined by pseudostratified columnar mucinous epithelium with varying degrees of cytological atypia. The IHC results showed positive for CK20, CEA, CDX-2, β-catenin, p53, MUC2 and MUC5AC, negative for PSA, AMACR, GATA3, MUC6, AR and NKX3.1 and variable expression for HMWCK and CK7. Genetic analysis revealed concurrent mutations of FAT1 (c.10001 T>C) and HNF1A in both cases. The similar morphology features of MPUAP and colorectal adenocarcinoma were seen. Membranous staining pattern of β-catenin and genetic mutation of FAT1 and HNF1A are two distinct features in MPUAP.